Uma análise sobre a relevância das empresas de pequeno porte na redução das desigualdades na distribuição de renda no Brasil - Benito, Paula Sewaybricker (2015)
This paper examines the role of Small and Medium Enterprises (SME s) on the Brazilian income distribution, based on municipal data between the years 2000 and 2010. The idea is to investigate if the SME s had an impact on the reduction of the high inequality of the country, through increasing labour income. The results we found show that on the poorer cities the SME s have a positive impact on income distribution. We also compare the evolution of SME s on the last decades in the BRICS countries. We conclude that the SME s have been increasing their participation on Brazilian economy and they have a very important role on the poorer cities